The Role of the Regional Disaster Management Agency in Flood Disaster Mitigation Efforts in Banyulegi Village, Dawarblandong District, Mojokerto Regency - Faulul Denisya Denisya; Diana Hertati (Universitas Muhammadiyah Ponorogo, 2024)
Banyulegi Village is an area that has the potential for flood disaster as it is a downstream area of the Kali Lamong River Basin. Consequently, this flood disaster instigates problems, both material and non-material damage and loss. Thus, it needs the role of the Regional Disaster Management Agency or BPBD of Mojokerto Regency in disaster mitigation efforts to reduce the risk and impact of flood disasters. This study applied a qualitative method with descriptive approach by using primary and secondary data obtained from observation, interviews, and documentation. The focus of this study is the role of the BPBD in disaster mitigation efforts based on the provisions of Mojokerto Regency Regent Regulation Number 102 of 2021 concerning Position, Organizational Structure, Main Duties and Functions and Work Procedures of the Regional Disaster Management Agency of Mojokerto Regency in the Prevention and Preparedness Sector Article (15) paragraph (1). The results of this study explain that the BPBD of Mojokerto Regency has carried out its role in mitigation efforts according to its duties and functions, including: 1) The role of BPBD in mitigation efforts through facilitation and outreach; 2) The role of BPBD in implementing cooperation with related agencies or institutions; 3) The role of BPBD in mitigation efforts through education and training; 4) The role of BPBD in mitigation efforts through simulation. There are several efforts to reduce flood disasters, through structural and non-structural mitigation. The inhibiting factor in this study was the activity of the village community, but this obstacle could be minimized through a joint decision between the BPBD of Mojokerto Regency and the village community. The supporting factor was the involvement of all elements of the Banyulegi Village community to participate in the activities as well as the related agencies or institutions that play a role in reducing disaster risk in Banyulegi Village.